Strategies and prospects for energy storage in future lunar base - Song Lei; Zhang Guoqing; Wang Yaohui; Wang Chang; Liu Bo (Advances in Mechanical Engineering, 2025)
Lunar energy storage systems face critical challenges from extreme thermal cycling (−173°C to 127°C) and prolonged darkness periods (354-hour nights). This study systematically evaluates three categories of lunar-compatible technologies: Electrochemical storage (lithium-ion batteries, regenerative fuel cells), Mechanical storage (flywheel arrays, compressed gas energy storage, molten salt reservoirs), Electromagnetic storage (supercapacitors, superconducting magnetic energy storage). However, standalone systems exhibit severe limitations: electrochemical devices show >35% capacity loss below −20°C, The energy storage efficiency of mechanical energy storage methods during the lunar night is relatively low, while electromagnetic solutions suffer from mass-specific energy deficits (<500 Wh/kg). We therefore propose a solar-driven hybrid architecture integrating: Daytime operations (1416 W/m 2 irradiance): 47% direct photovoltaic power for base loads; 5.6% of the energy is used for the regenerative fuel cell system; 3.7% of the energy is used for flywheel acceleration; 26.5% of the energy is used for battery charging; 17.3% of the energy is used for lifting heavy objects. Nighttime operations: Predominantly using battery energy storage, gravitational energy storage, and molten salt energy storage systems to provide a combined 89.8% of the electrical energy for the lunar base. The integrated energy storage system has a stable energy supply, can effectively respond to changes in the lunar environment, improve resource utilization efficiency, and prolong the service life of the equipment. It provides a scientific and feasible reference scheme for the lunar energy storage strategy.